THE EFFECT OF BOILED BITTER MELON FRUIT ON REDUCING BLOOD SUGAR LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - Maharani Eka Putri; Andre Utama Saputra; Erik Rosadi; Sasono Mardiono (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Diabetes Mellitus is where the glucose level experiences an abnormal increase reaching above ≥ 200 mg/dl and there can be a risk of complications up to death. The aim of the study was to examine the effect of consuming bitter melon stew on lowering blood glucose for people with Type 2 Diabetes. In this analysis, a Quasy Experimental design was used using the Two Group method, involving an intervention group and a control group, and measurements were taken before (Pre-Test) and after (Post-Test) the intervention. The total number of samples in this study was 44 respondents. This study applies the Purposive Sampling technique in sampling selection and was carried out in the period 2 to 17 July 2024. This research analyzed data using the Paired T-Test and the Independent Samples T-Test. The impact of this study indicates that the p value = 0.000 < 0.05, which is intended to explain the existence of a substantial effect on blood glucose in people with Type II Diabetes after consuming bitter melon boiled fruit.